Simulation of wave scattering over a floating platform in the ocean with a coupled CFD-IBM model - Pengxuan Luo; Jingxin Zhang; Yongyong Cao; Shaohong Song (Theoretical and Applied Mechanics Letters, 2024)
A numerical study of linear wave scattering over a floating platform has been simulated by an efficient numerical model in this letter. The non-hydrostatic model is used to simulate the free surface and the uneven bottom. For the solid body modelling, the immersed boundary method (IBM) is implemented by introducing a virtual boundary force into the momentum equations to emulate the boundary conditions. This implementation enhances the ability of the model to simulate interactions between waves and floating structures. A numerical case involving wave interactions with a floating platform is studied to validate the numerical model. By simulating the wave propagation, the numerical model captures the variation of the wave scattering very well, which verifies the performance of the numerical model and the robust strategy of the IBM.